Grigol II (Lortkipanidze) - Catholicos of Abkhazia (Western Georgia) - Lortkipanidze, Irakli (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
The Diocese of Abkhazia in Western Georgia has played a significant role in the history of the Apostolic Autocephalous Orthodox Church of Georgia. Throughout its existence, it was led by numerous distinguished hierarchs. From 1696 to 1742, Grigol II (Lortkipanidze) served as the Catholicos of Abkhazia for a remarkable period of 46 years. Various charters, archival materials, and museum documents provide valuable information about the life and activities of Grigol II, the Catholicos of Abkhazia. In 1701, Dosítheos, the patriarch of Jerusalem, sent a letter to Grigol II, acknowledging his position as the Catholicos of Abkhazia. Pope Clement XI also informed SulkhanSaba Orbeliani and Catholicos Grigol Lortkipanidze about sending missionaries to Abkhazia and sought their assistance. Grigol II undertook the restoration of agriculture that belonged to the Diocese of Abkhazia and reclaimed some of the estates seized by feudal lords in Odishi, Guria, and Racha. He notably provided support to the oppressed Catholic serfs who were forcibly relocated across the Enguri River. Grigol II actively participated in the political affairs of the time. As the leader of the Church in Western Georgia, Grigol Lortkipanidze is referred to as both Catholicos and Patriarch. Grigol II, the Catholicos of Abkhazia, passed away in 1742. Renowned writer and theologian Nikoloz Cherkezishvili-Rustveli composed a eulogistic sermon highlighting the merits of Grigol Lortkipanidze in his iambic verse. This article draws upon museum documents and scholarly literature, some of which are being introduced into academic circulation for the first time.